2016
DOI: 10.1111/cei.12875
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for successful cancer immunotherapy in aged hosts

Abstract: Summary Immunotherapy is now experiencing unprecedented successes in treating various cancers based on new understandings of cancer immunopathogenesis. Nonetheless, although ageing is the biggest risk factor for cancer, the majority of cancer immunotherapy preclinical studies are conducted in young hosts. This review will explore age‐related changes in immunity as they relate to cancer immune surveillance, immunopathogenesis and responses to immunotherapy. Although it is recognized that declining T cell functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 115 publications
(149 reference statements)
1
32
0
Order By: Relevance
“…The most important of these receptors are PD-1, CTLA-4, LAG-3, TIM-3, and TIMIN. This distinction has gained considerable importance since it has been reported that a number of cancers in some elderly subjects could be successfully modulated and T cells engineered to be immunotoxic toward such cancers, namely melanoma and NSCLC ( 80 82 ).…”
Section: Immune Changes With Aging: Immunosenescence and Inflamm-aginmentioning
confidence: 99%
“…The most important of these receptors are PD-1, CTLA-4, LAG-3, TIM-3, and TIMIN. This distinction has gained considerable importance since it has been reported that a number of cancers in some elderly subjects could be successfully modulated and T cells engineered to be immunotoxic toward such cancers, namely melanoma and NSCLC ( 80 82 ).…”
Section: Immune Changes With Aging: Immunosenescence and Inflamm-aginmentioning
confidence: 99%
“…As we dissect components and interactions in more detail, the research enterprise can begin to embrace variation to learn better from animal models [223,224] and humans [225,226] , including with respect to age [227] . Data sharing can help ensure technical advances are employed towards broad evidence-based progress [228] .…”
Section: Monitoring and Modelingmentioning
confidence: 99%
“…Finally, it is well known that cancer incidence increases with age. Measures of aging in the immune system [294] could potentially be used to predict tumor/immune interactions and guide treatment decisions [295] .…”
Section: Systemic Immune Responsementioning
confidence: 99%